Pengaruh Aktivitas Pasar Wae Kesambi Terhadap Kinerja Ruas Jalan Batu Cermin Labuan Bajo, Kabupaten Manggarai Barat - Hartutut , Awanda; Arifianto , Andy Kristafi; Rahma , Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Pasar wae kesambi is one of the traditional markets of the city of labuan bajo which is located on Jalan Batu Cermin, Batu Cermin sub-district, Komodo Kab.Manggarai Barat. Pasar wae kesambi is among the most crowded markets in labuan bajo, because the market is a meeting area between traders and bidders will negotiate trade in goods or services. This market can be said to be a people's market because it only sells the needs of the community. The high side obstacles every hour of this market affect the performance of road traffic and result in a decrease in speed and disruption of road user activities when crossing the Jalan Di Pasar Wae Kesambi Labuan Bajo, West Manggarai Regency. One of the problems that contribute to deepening the traffic situation, is the problem of side interference on road bodies with a lot of traffic flow. The purpose of this study is to understand how the ability of the mirror stone road section, the influence of side obstacles and how solutions to improve the ability of the road section. From the calculation of the study of the Indonesian Road Capacity guidelines obtained very high side obstacles (H) = 40,000 event weight. For the performance of the Jalan Batu Cermin section, it can meet the total traffic volume = 962,25 skr/h. The Jalan Batu Cermin road section is said to experience problems due to side obstacles with a degree of saturation capacity of 0.94 skr/hour.